Preoperative Transjugular Intrahepatic Portosystemic Shunt Placement for Extrahepatic Abdominal Surgery - Philip, Michelle; Thornburg, Bartley (Seminars in Interventional Radiology, 2018)
Extrahepatic abdominal surgery in patients with portal hypertension is associated with a high rate of perioperative complications and death due to the increased risk of liver failure, perioperative bleeding, and ascites. One proposed method to facilitate surgery in these patients is with preoperative placement of a transjugular intrahepatic portosystemic shunt (TIPS). By decompressing the portal circulation, this presurgical measure would theoretically decrease the potential for bleeding and improve the ability to control ascites in the perioperative and postoperative period. This article reviews the use of TIPS prior to abdominal surgery in patients with portal hypertension.
Keywords: TIPS; portal hypertension; abdominal surgery